EVALUATION THE EFFICACY OF SOME AMINO ACIDS IN NORMAL AND NANO FORMS IN DUCING RESISTANCE IN TOMATO PLANTS AGAINST ROOT-KNOT NEMATODE MELOIDOGYNE SPP.: EVALUATION THE EFFICACY OF SOME AMINO ACIDS IN NORMAL AND NANO FORMS IN DUCING RESISTANCE IN TOMATO PLANTS AGAINST ROOT-KNOT NEMATODE MELOIDOGYNE SPP. (Iraqi Journal of Market Research and Consumer Protection, 2025)
This study was conducted to evaluate the role of certain plant elicitors of normal and Nano amino acids in inducing systemic defenses against root-knot nematodes in tomato plants in greenhouse conditions. All treatments showed high efficacy, and the inhibitory effect of the tested acids on nematode root-knot Reproduction was positively correlated with increasing concentration. Additionally, plant growth was enhanced by all the treatments in general. Arginine and Serine at a concentration  20 and 30 ppm respectively recorded the highest stimulation peroxidase enzyme activity after 9 days of treatment with significant differences in quantity (21.28,21.56 min / gm fresh ) compared to the control treatment that It recorded (19.14 min/g fresh ), while the highest stimulation of Phenyl alanine ammonia-lyase enzyme activity was recorded for the same two acids at the same higher concentrations (16.78,18.31 mg cinnamic per hour) compared to the comparison treatment, which was (11.02 min/fresh weight). The higher concentration of the two acids above was the evidence of complexation. the severity of the infection was (1.41, 1.08) and the severity of the infection were (33.33, 27.08)%. Compared to the control treatment, which was 3.41, as evidenced by the complexity and severity of infection was 85.41%, while all the tested treatments recorded a significant superiority in the wet and dry weight of the shoot and the amount of chlorophyll concentration, compared to comparison treatment. Which recorded the highest percentage of the wet root system, which was to 23.84 g/ wet. All tested amino acids had a significant effect on the development and alleviation of the disease.